2006
DOI: 10.1007/s00439-005-0129-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel heterozygous deletion in the EVC2 gene causes Weyers acrofacial dysostosis

Abstract: Weyers acrofacial dysostosis (MIM 193530) is an autosomal dominant disorder clinically characterized by mild short stature, postaxial polydactyly, nail dystrophy and dysplastic teeth. Ellis-van Creveld syndrome (EvC, MIM 225500) is an autosomal recessive disorder with a similar, but more severe phenotype. Mutations in the EVC have been identified in both syndromes. However, the EVC mutations only occur in a small proportion of EvC patients. Recently, mutations in a new gene, EVC2, were found to be associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…The Weyers acrofacial dysostosis, an autosomal dominant disorder described in 1952, is characterized by variable extremities and facial features. This condition has been found to be associated with EVC and EVC2 mutations that, finally, confirmed that Weyers dysostosis represents the heterozygous expression of the mutation, which, in homozygous form, causes the autosomal recessive disorder EVC [23,24]. …”
Section: Clinical Descriptionmentioning
confidence: 60%
“…The Weyers acrofacial dysostosis, an autosomal dominant disorder described in 1952, is characterized by variable extremities and facial features. This condition has been found to be associated with EVC and EVC2 mutations that, finally, confirmed that Weyers dysostosis represents the heterozygous expression of the mutation, which, in homozygous form, causes the autosomal recessive disorder EVC [23,24]. …”
Section: Clinical Descriptionmentioning
confidence: 60%
“…There are two misssense changes, I283R and A1045V, and one 205 amino acid in-frame deletion. It has recently been shown that a heterozygous deletion (c.3793delC) in the Wnal coding exon (exon 22) of EVC2, which creates an immediate premature termination codon, gives rise to the Weyer's phenotype (Ye et al 2006). As the mutant mRNA species contains the premature termination codon in the Wnal coding exon, the transcript should not be destroyed by nonsense mediated decay (Hentze and Kulozik 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in both genes include single-basepair substitutions, microinsertions, microdeletions, and few deletions spanning more than one exon within the same gene [Tompson et al, 2007]. Two changes, S307P in EVC and c.3793delC in EVC2, were respectively found in pedigrees with autosomal dominant Weyer's acrodental dysostosis (MIM] 193530) demonstrating that specific mutations in EVC or EVC2 have a dominant negative effect [Ruiz-Perez et al, 2000;Ye et al, 2006]. Weyer's patients have postaxial polydactyly and dental anomalies but not the short stature and cardiac manifestations of EvC.…”
Section: Introductionmentioning
confidence: 98%